A standardized, extensible framework for optimizing classification improves marker-gene taxonomic assignments - Bokulich, Nicholas A; Rideout, Jai Ram; Kopylova, Evguenia; Bolyen, Evan; Patnode, Jessica; Ellett, Zach; McDonald, Daniel; Wolfe, Benjamin; Maurice, Corinne F; Dutton, Rachel J; Turnbaugh, Peter J; Knight, Rob; et al. (PeerJ PrePrints, 2015)
Background: Taxonomic classification of marker-gene (i.e., amplicon) sequences represents an important step for molecular identification of microorganisms. Results: We present three advances in our ability to assign and interpret taxonomic classifications of short marker gene sequences: two new methods for taxonomy assignment, which reduce runtime up to two-fold and achieve high precision genus-level assignments; an evaluation of classification methods that highlights differences in performance with different marker genes and at different levels of taxonomic resolution; and an extensible framework for evaluating and optimizing new classification methods, which we hope will serve as a model for standardized and reproducible bioinformatics methods evaluations. Conclusions: Our new methods are accessible in QIIME 1.9.0, and our evaluation framework will support ongoing optimization of classification methods to complement rapidly evolving short-amplicon sequencing and bioinformatics technologies. Static versions of all of the analysis notebooks generated with this framework, which contain all code and analysis results, can be viewed at http://bit.ly/srta-010.
Keywords: bioinformatics; microbiome; executable paper; qiime; rRNA; ITS; microbial ecology; fungal diversity; bacterial diversity